The Practice of Children’s Rights Protection in the Americas - Zombory, Katarzyna (Children’s Rights in Regional Human Rights Systems, 2024)
In the Inter-American Human Rights Protection System, children are entitled to special protection measures guaranteed in the principal human rights instruments adopted under the auspices of the Organization of American States (OAS). These include the 1948 American Declaration on the Rights and Duties of Man and the 1969 American Convention on Human Rights. State compliance with human rights is overseen by the Inter-American Commission on Human Rights (IACmHR) and the Inter-American Court of Human Rights (IACtHR), which are empowered to receive and consider complaints of human rights violations. This chapter presents an overview of the IACmHR’s and IACtHR’s case law on children’s rights, as well as the main conceptual framework relating to children’s rights protection in the Americas, such as the right to complementary protection or the best interests of the child. It also addresses the treatment of children in different vulnerable situations (e.g. street children, Indigenous children, children deprived of liberty, and girls) as developed in the jurisprudence of the main Inter-American human rights treaty bodies. Keywords: children’s rights, Inter-American System of Human Rights, Inter-American Commission on Human Rights, Inter-American Court of Human Rights